Optimization of building microgrid energy system based on virtual energy storage - Lv, Guangxian; Ji, Yu; Zhang, Ying; Wang, Wenbo; Zhang, Jie; Chen, Jikai; Nie, Yonghui (Frontiers in Energy Research, 2023)
With the continuous development of building microgrids, it is crucial to explore and study the energy-saving potential of buildings to resolve energy shortages and environmental protection problems. Therefore, to realize the efficient and economical operation of a building microgrid, a new multi-objective optimization method is proposed for the planning and operation of building microgrid considering virtual energy storage. First, virtual energy storage model of the building microgrid is established based on the heat storage characteristics of the building itself. Second, a multi-objective optimization model of the building microgrid considering virtual energy storage is constructed by considering the investment cost and the comprehensive operation benefits as the objectives as well as the constraints of cooling, heating, power balance. Finally, based on the original gray wolf swarm algorithm, the niche processing mechanism and gray weighted correlation method are introduced to optimize the configuration and operation of the building microgrid. For a typical building microgrid in summer and winter, the simulation results reveal that the proposed method improves the overall economy of planning the building microgrid system and its operation and user experience via virtual energy charge and discharge management.